2016
DOI: 10.29252/ijrm.14.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Survey on association between Mycoplasma hominis endocervical infection and spontaneous abortion using Polymerase Chain Reaction

Abstract: Background:Mycoplasma infections are suggested as etiology of adverse pregnancy outcomes. Objective:The aim of this study was to evaluate the association of Mycoplasma hominis (M. hominis) infection and spontaneous abortion among pregnant women.Materials and Methods:In this case-control study that was conducted from August 2012 to January 2013, totally, 109 women were included with spontaneous abortion with gestational ages of 10-20 weeks (Cases), and 109 women with normal pregnancy with gestational ages betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…However, a direct relationship with the development of abortion was not observed. In other studies, the results were also similar [24, 28]. These microorganisms are often found in the genital tract of pregnant women, where they can invade the placenta and contribute to the development of abortion.…”
Section: Discussionsupporting
confidence: 80%
“…However, a direct relationship with the development of abortion was not observed. In other studies, the results were also similar [24, 28]. These microorganisms are often found in the genital tract of pregnant women, where they can invade the placenta and contribute to the development of abortion.…”
Section: Discussionsupporting
confidence: 80%
“…The study reported that M. hominis and U. urealyticum were present in 5% and 3% of the chorionic villi samples, which was much lower than that reported in the present study [17]. Farhadifar et al [18] and Ramazanzadeh et al [19] reported much lower rate of M. hominis. These studies evaluated the association between M. hominis and spontaneous abortion in 109 women.…”
Section: Discussioncontrasting
confidence: 69%
“…They are beta-lactam-resistant due to the absence of a cell wall, and their high nutritional demand makes them difficult to culture [1,2], although this problem has recently been solved by applying molecular techniques. They are often found as colonizers of mucosae, mainly respiratory and genitourinary [3,4]. Mycoplasma hominis was the first of various human pathogen species to be isolated.…”
Section: Introductionmentioning
confidence: 99%